Human Impacts on Ancient Marine Ecosystems : A Global Perspective - Erlandson, Jon; Rick, Torben C. (Book collections on Project MUSE., 2008)
"Archaeological data now show that relatively intense human adaptations to coastal environments developed much earlier than once believed - more than 125,000 years ago. With our oceans and marine fisheries currently in a state of crisis, coastal archaeological sites contain a wealth of data that can shed light on the history of human exploitation of marine ecosystems and marine conservation principles. This volume, the first global survey of these topics, brings together researchers working in coastal areas around the world to address the links between archaeology, history, marine ecology, and fisheries management. In eleven case studies from the Americas, the Pacific Islands, the North Sea, the Caribbean, Europe, and Africa, they cover diverse marine ecosystems ranging from kelp forests to coral reefs and mangroves and reach into deep history to discover how humans interacted with and affected these aquatic environments."--Jacket.